Insights into the structural perturbations of spliced variants of CD44: a modeling and simulation approach. Issue 2 (25th January 2017) - Patel, Shanaya; Shaikh, Faraz; Devaraji, Vinod; Radadiya, Ashish; Shah, Kanisha; Shah, Anamik; Rawal, Rakesh
Abstract : Transient interactions between cancer stem cells and components of the tumor microenvironment initiate various signaling pathways crucial for carcinogenesis. Predominant hyaluronan (HA) receptor, CD44 is structurally and functionally one of the most variable cell surface receptors having the potential to generate a diverse repertory of CD44 isoforms by alternative splicing of variant exons and post-translational modifications. A structurally distinctive variant of CD44, CD44v10, has an inevitable role in malignant progression, invasion, and metastasis. This can be attributed to the binding of HA with CD44v10, which demonstrates a completely different behavioral pattern as compared to the other spliced variants of CD44 molecule. Absence of a comprehensively predicted crystal structure of human CD44s and CD44v10 is an impediment in understanding the resultant structural alterations caused by the binding of HA. Thus, in this study, we aim to predict the CD44s and CD44v10 structures to their closest native confirmation and study the HA binding-induced structural perturbations using homology modeling, molecular docking, and MD simulation approach. The results depicted that modeled 3D structures of CD44s and CD44v10 isoforms were found to be stable throughout MD simulations; however, a substantial decrease was observed in the binding affinity of HA with CD44v10 (−5.355 kcal/mol) as compared to CD44s. Furthermore, loss and gain of several H-bonds and hydrophobic interactions in CD44v10–HA complex during the simulation process not only elucidated the reason for decreased binding affinity for HA but also prompted toward the plausible role of HA-induced structural perturbations in occurrence and progression of carcinogenesis. Abstract :